Synthesis and Magnetic Characterization of Graphite-Coated Iron Nanoparticles - Espinoza Rivas, A. Mauricio; Pérez Guzmán, Manuel A.; Ortega Amaya, Rebeca; Santoyo Salazar, J.; Gutiérrez Lazos, Claudio Davet; Ortega López, Mauricio (2016)
Graphite-coated iron nanoparticles were prepared from magnetite nanoparticles by chemical vapour deposition (CVD) under methane and hydrogen atmosphere. After being purified from carbon excess, graphite-coated iron nanoparticles were tested for morphological and magnetic properties. It was found that, during the thermal process, magnetite nanoparticles 6 nm in size coalesce and transform into graphite-coated iron 200 nm in size, as revealed by scanning electron microscopy (SEM). Raman characterization assessed that high-quality graphite coats the iron core. Magnetic measurements revealed the phase change (magnetite to iron) as an increase in the saturation magnetization from 50 to 165 emu/g after the CVD process.